Лінгвософська рецепція декодування документального кінотексту (на прикладі фільмів про Лесю Українку) - Ганжа, А. (Культура слова, 2020)
У статті зроблено спробу окреслити окремі лінгвософські засади декодування документального кінотексту як різновиду гетерогенних текстів. Рецепція й аналіз лінгвальних та нелінгвальних кодів кінотексту стрічок «Великі українці. Леся Українка» (2007), «Вір мені» (2005), «Леся Українка. Місія» (2011) спроєктовані на специфіку реалізації мовних маркерів інфотейнменту. Висловлено гіпотезу, що інфотейнмент – це універсальний стиль творчої діяльності, що нині пронизує різні тематичні сфери, зосібна – кінодокументалістику. In the modern information space of the beginning of the XXI century, verbal communication is increasingly combined with various nonverbal ways of transmitting information. Currently in the field of view of researchers heterogeneous texts characterized by a polycode structure. Different recipients decode the same heterogeneous text with varying degrees of depth and adequacy. Traditionally, the following factors influencing the decoding process are distinguished: personal characteristics of the recipient of the heterogeneous text; parameters of the heterogeneous text and the reality reflected in it; the specifics of the situation in which the decoding takes place. Among heterogeneous texts, a special place belongs to film text, the decoding of which is always variant, as it depends on the perception of a particular viewer, and occurs at the level of the text (verbality) and at the level of other means of expression (nonverbality). The polycode nature of modern communication has a powerful influence on the culture of society and linguistic culture in particular, which is primarily manifested in media production. In the broad sense, infotainment is a way of presenting information in an entertainment form based on the hedonistic function of the media and appealing to the audience’s emotions. The most widespread linguistic techniques of infotainment are language play, expressiveness, irony, suspense, dramatization. They are aimed at ensuring the dynamism and creativity of the plot, emotional influence, saturation with means of expressiveness. For linguistic analysis, we consider the term “language marker” of infotainment to be more correct, since linguists deal with a ready-made, already established media product, in which certain language tools mark (indicate, help identify) the format of infotainment, whereas social communication specialists study the mechanisms for creating media products in this format. According to the results of the study, the language markers of infotainment in documentary movies are expressed and concealed, can be correlated or contrast with the video, but they are combined by a pragmatic approach to establish contact with the recipient, to attract and to retain his attention.